2021
DOI: 10.3390/ijerph18073690
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Food Environment Healthiness Score: Development, Validation, and Testing between Different Types of Food Retailers

Abstract: The aim of this study was to develop and validate a scoring system, based on AUDITNOVA, to assess the healthiness of the consumer food environment, considering food availability, price, advertising, and placement strategies. Audited data of 650 food retailers were used to develop, validate, and test the consumer food environment healthiness score. To compose the score, the reference was the Dietary Guidelines for the Brazilian Population. The total and subscores were standardized for a scale from 0 to 100. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
0
23
0
11
Order By: Relevance
“…The guiding framework described by Khandpur et al is therefore an important and timely addition to the literature [ 31 ••]. Some of the elements in the framework align with the myriad auditing/assessment tools developed for use in physical retail environments [ 4 , 9 •, 10 , 45 – 48 ]. This is clearly seen in the studies identified through this review, which largely applied or adapted existing methods for evaluating the 4Ps in physical stores.…”
Section: Discussionmentioning
confidence: 99%
“…The guiding framework described by Khandpur et al is therefore an important and timely addition to the literature [ 31 ••]. Some of the elements in the framework align with the myriad auditing/assessment tools developed for use in physical retail environments [ 4 , 9 •, 10 , 45 – 48 ]. This is clearly seen in the studies identified through this review, which largely applied or adapted existing methods for evaluating the 4Ps in physical stores.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of creating a score to assess the availability of ultra-processed foods in the consumer food environment came from another study carried out in Brazil by Borges et al ( 46 ), which developed and tested a score to assess the healthiness of the consumer food environment considering factors such as food availability, price, advertising, and placement strategies in the final score composition. When testing the healthiness score in a sample of food retailers, the authors found that butchers and fishmongers and public specialized fresh food market indoor have the best healthiness indexes and are the places that could favor the best food choices.…”
Section: Discussionmentioning
confidence: 99%
“…Other instruments and indicators have been adopted to measure the consumer food environment with a focus on the assessment of facilitators for the consumption of healthy foods, with availability, prices, and information of healthy foods in establishments such as convenience stores, markets, and grocery stores [ 45 , 46 , 47 ]. More recently, an audit tool based on the NOVA classification (AUDITNOVA) was developed for the assessment of the retail food trade [ 21 , 23 ]. All the above-mentioned instruments were developed to characterize the retail food establishments (supermarkets, grocery stores) and they are, thus, not adequate for the assessment of establishments that sell foods for immediate consumption.…”
Section: Discussionmentioning
confidence: 99%
“…There are still few studies that present summary measures for the assessment of the consumer food environment [ 13 ]. Most summary indicators proposed in these studies are only applicable in certain types of establishments that sell foods to be consumed later, such as supermarkets [ 20 , 21 , 22 , 23 , 24 ]. Besides, the construction of these measures is quite complex [ 21 , 23 , 25 ], which hinders their large-scale use and/or application to specific realities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%